Management and Development of Ngargoretno Tourism Village in Sustainability Aspects - Robi Hari Marhesa; Luchman Hakim; Edriana Pangestuti (Indonesian Journal of Environment and Sustainable Development, 2021)
This study aims to determine the management and development efforts that the management and related stakeholders have carried out in sustainability aspects, both environmental, economic, and social aspects. The method used in this research is descriptive qualitative analysis. Data collection techniques through interviews, observation, and literature study. The determination of sources is done by purposive sampling. The development efforts that have been carried out in environmental aspects are: 1) prioritizing the vision of environmental conservation in tourism development; 2) carrying out reforestation activities; 3) making tourism village regulations and prohibiting bird hunting; 4) implementing environmental clean program; and 5) regulate the number of visitors. Efforts in the economic aspect are: 1) provide an understanding of the economic potential in tourism activities; 2) offer tourism attractions based on community economic activities; 3) develop local products; 4) conduct tourism promotion; 5) establish BUMDES (Village Owned Enterprises) (Village Owned Enterprises) as the management and marketing agency; and 6) open cooperation with the private sector. Based on the social aspects include: 1) socialization of the tourism sector; 2) increasing the capacity of human resources; 3) forming a tourism awareness group; 4) involving residents in tourism activities, and 5) developing cultural tourism. Keywords: tourism village, sustainability, development